Integrated process for preparing porous, surface functionalized polyetherimide microparticles‡. (December 2015) - Basu, Sayantani; Heuchel, Matthias; Weigel, Thomas; Kratz, Karl; Lendlein, Andreas
Abstract : Highly porous polyetherimide (PEI) microparticles achieved by a spraying/coagulation process are candidate absorber materials for apheresis applications. Hydrophobic PEI surfaces tend to be rapidly coated with proteins when in contact with blood. Therefore, a hydrophilic modification of such particles is required. In this study, we explored the formation of porous, surface functionalized PEI microparticles by low molecular weight polyethyleneimine (Pei) or potassium hydroxide (KOH) in an integrated process combining chemical modification and particle formation. The integrated process resulted in smaller microparticles with diameters of 70 to 80 µm compared to the chemical two‐step process. All particles exhibited similar bulk densities, ranging from 0.09 to 0.015 g cm −3, and average pore sizes around 180–250 nm. A successful modification of the particles' surface by both processing approaches could be confirmed by X‐ray photoelectron spectroscopy measurements and microwetting experiments, where hydrophilic advancing contact angles of 57° to 64° were determined. Integrated particle processing further resulted in changes of the bulk properties, i.e. molecular weight, thermal decomposition behavior or glass transition temperature. Hydrophilic modified PEI microparticles have been successfully prepared by different approaches. In a next step their absorption capacity for uremic toxins will be investigated with regard to a potential application in blood detoxification. Copyright © 2015 John Wiley & Sons, Ltd.